«To bring light to the pious reader»: references to information sources and transmission of knowledge in the artistic recipe book by João Stooter (1729-1732) - René Lommez Gomes (Bibliothecae.it, 2021)
Born in Antwerp and living in Portugal, the diamond cutter João Stooter acquired some prominence in the 18th century when he produced an armory manual and an artistic recipe book. His works were intended to improve the quality of the products created by the Kingdom’s mechanical officers and artists, making them rival foreign products. Regarding his second work, an artistic how-to-do book entitled «Arte de Brilhantes Vernises», the author found himself moved to write on a wide range of subjects – such as varnishes, paints, and glues – relating to the artisanal transformation of raw materials that the overseas trade dumped on the Portuguese market, such as wood from Brazil and Africa. At the dawn of Portuguese Illustration, Stooter gathered, tested and corrected recipes for varnishes and other artistic compounds obtained from a wide range of information sources, above all in various genres of printed books. With the result of the experiments conducted in his studio, which aimed at testing, correcting and standardizing the preparations and techniques, he composed the first recipe book of its kind to be printed in Portuguese. The work was edited by the Verdussen house, in Antwerp, between 1729 and 1732. Several copies of it were later enhanced with handwritten notes by the author. In printed and manuscript texts – which were born from his bibliographic gesture, when selecting, compiling and mediating previous records – the author developed a complex system of internal references to the contents of the book and to works taken as a source, which required the technical gesture of the artisan if added to the indicated reading path, so that a preparation could be carried out satisfactorily. Based on the proposition that the field of bibliography encompasses the history of production and uses of books, this study will demonstrate how the references defined this recipe book model, placing itself at the center of the transmission of artisanal knowledge advocated in the work.